2020
DOI: 10.3390/ma13071686
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Derived Nitrogen Doped Carbon Nanotubes for Efficient Oxygen Reduction Reaction and Arsenic Removal from Contaminated Water

Abstract: Nitrogen doped carbon nanotubes (NCNT) that were prepared by simple microwave pyrolysis of Niacin (Vitamin B3) as noble metal free electrocatalyst for oxygen reduction reaction (ORR) is reported. Our newly developed technique has the distinct features of sustainable and widely available niacin as a bi-functional source of both carbon and nitrogen, whereas the iron catalyst is cheap and the fourth most common element in the Earth’s crust. The results of the electrochemical tests show that our newly developed ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…Till date, organically modified nano-clays have been the most prevalent catalyst support, the primary reason being the layered structure of nano-clay impedes the fast escape of gases by “tortuous path” and helps in retention of catalyst particles. Graphene, the newest allotrope of carbon, first isolated by Geim and Novosalev [ 26 ], which when combined with metals either as 0-D quantum dots [ 27 ], 1-D nano-particles [ 28 ], 2-D nano-tubes [ 29 ] or 3-D clusters such as nano-flowers [ 29 ] have been reported in applications such as catalysis [ 30 ], energy storage devices [ 31 ], sensors [ 32 ], etc. Of these, graphene-CNT hybrids have proven to perform excellently in energy storage devices such as super-capacitors [ 33 ], electrodes in sodium-ion batteries [ 34 ], catalysts for ORR reactions [ 35 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Till date, organically modified nano-clays have been the most prevalent catalyst support, the primary reason being the layered structure of nano-clay impedes the fast escape of gases by “tortuous path” and helps in retention of catalyst particles. Graphene, the newest allotrope of carbon, first isolated by Geim and Novosalev [ 26 ], which when combined with metals either as 0-D quantum dots [ 27 ], 1-D nano-particles [ 28 ], 2-D nano-tubes [ 29 ] or 3-D clusters such as nano-flowers [ 29 ] have been reported in applications such as catalysis [ 30 ], energy storage devices [ 31 ], sensors [ 32 ], etc. Of these, graphene-CNT hybrids have proven to perform excellently in energy storage devices such as super-capacitors [ 33 ], electrodes in sodium-ion batteries [ 34 ], catalysts for ORR reactions [ 35 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…A similar synthesis procedure as described in Section 2.2 with substitution of graphene oxide dispersion with carbon fiber is used. However, before use the commercially available CFs were washed successively with 10% HCl and DI water to remove any commercial 'sizing' materials and dipped in Mn-H3BTC stock solution for 30 min which were subsequently removed and dried in oven at 70 °C to obtain Mn-H3BTC MOF decorated carbon fibers (representative XRD and SEM in Figures S1 and S2 of Supplementary File, respectively) which all investigated pH values, our MnO2@CNT-CF nanostructures showed comparable adsorption capacity and when compared with our previously reported Fe@CNT-CF [70]. The well dispersed MnO2 nano-particles in open pore hybrid network of carbon nanotubes vertically anchored on carbon fiber substrate increases the active surface area and facilitates for the optimal capture and retention of arsenic moieties.…”
Section: Resultsmentioning
confidence: 52%
“…In this manuscript we report for the first time the utility of manganese oxide-CNT on carbon fibers as possible adsorbent of arsenic. The rate of adsorption at various concentrations by our novel MnO 2 @CNT-CF adsorbent is plotted in Figure 5 d which shows that at all investigated pH values, our MnO 2 @CNT-CF nanostructures showed comparable adsorption capacity and when compared with our previously reported Fe@CNT-CF [ 70 ]. The well dispersed MnO 2 nano-particles in open pore hybrid network of carbon nanotubes vertically anchored on carbon fiber substrate increases the active surface area and facilitates for the optimal capture and retention of arsenic moieties.…”
Section: Resultsmentioning
confidence: 69%
“…In contrast, the base was substantially narrower and is consistent with observations of O’Byrne et al who reported a similar phenomenon in nitrogen-doped CNT synthesized from nitrogenated precursors [ 22 , 23 ]. HRTEM of the CNT at the tip exhibited in Figure 1 f indicates presence of highly graphitized inner 22–24 walls, whereas the outermost 3–4 walls were comparatively less graphitized, disordered with interstitial defects, which can be attributed to the ‘knock-on effect’ of microwave radiation, which can damage and dislodge a carbon atom from the walls of CNT [ 24 ]. A dark-field TEM image of Figure 1 d and its corresponding iron and nitrogen maps are shown in Figure 1 g,h,i, respectively, wherein the metal nanostructures anchored on rGO and embedded inside the walls of CNT appear brighter, whereas the carbon moieties appear transparent.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, synthesis of 3DCNS from calcination and pyrolysis of MOF in conjunction with graphene [19], carbon fibers [20], metal nanowires [21], nanoplatelets [22] etc. has been reported.…”
Section: Introductionmentioning
confidence: 99%